2022
DOI: 10.1080/21645515.2022.2106720
|View full text |Cite
|
Sign up to set email alerts
|

Expert consensus on the role of OM-85 in the management of recurrent respiratory infections: A Delphi study

Abstract: Recurrent infections of upper and lower respiratory tract have an important clinical and economic impact, which can be reduced through appropriate preventive measures, including the use of immunomodulating agents, such as OM-85, which proved to be effective and safe in both adults and children. Although OM-85 can be useful for the prevention of respiratory tract infections, it is still underused in clinical practice. In order to evaluate the level of awareness of the disease burden of recurrent respiratory inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 37 publications
1
4
0
2
Order By: Relevance
“…In a further study regarding the efficacy and tolerability of influenza vaccine in combination with OM-85 [ 17 ] a significant advantage of the combined prevention could be detected compared to the single prevention arm. This finding was additionally supported by the recently online published expert consensus on the role of OM-85 in the management of recurrent respiratory infections [ 18 ].…”
Section: Group 72: Paediatric Asthma and Allergysupporting
confidence: 54%
“…In a further study regarding the efficacy and tolerability of influenza vaccine in combination with OM-85 [ 17 ] a significant advantage of the combined prevention could be detected compared to the single prevention arm. This finding was additionally supported by the recently online published expert consensus on the role of OM-85 in the management of recurrent respiratory infections [ 18 ].…”
Section: Group 72: Paediatric Asthma and Allergysupporting
confidence: 54%
“…Prevention is widely recognized as the most important intervention in reducing the disease burden associated with repeated respiratory tract infections in children. Since the elimination of environmental triggering factors is unfeasible, immunotherapy is considered the most effective preventative strategy [ 30 ]. Our results suggest that the bacterial preparations assessed in the present study were highly effective for this purpose, which could mean significant reductions of the associated clinical [ 1 , 31 ] and financial [ 5 ] burdens, antibiotic prescription and resistance [ 32 , 33 ], and medical complications [ 2 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Most studies have shown it to be protective against recurrent upper respiratory tract infections [ 6 , 16 , 18 , 39 37 -] despite some conflicting reports [ 40 ], which could be partially explained by the various methods by which the lysates were prepared [ 41 ]. Notwithstanding this considerable amount of favorable evidence concerning the use of this product in upper respiratory tract infections, it is still seldom recommended for ENT infections and in general is not shared among clinicians [ 30 ]. The promising results in our study support the broader recommendation of immunotherapy for the prevention of ENT infections.…”
Section: Discussionmentioning
confidence: 99%
“…In this respect, OM-85 is recognized as the most studied immunomodulatory agent currently available, whose efficacy makes it a valuable tool. 6 In particular, the combined use of OM-85 and vaccination was recognized as an effective approach to improve prevention strategies in order to reduce the burden of recurrent respiratory infections associated with wheezing episodes. 6 …”
Section: Recurrent Wheezing or Reactive Airwaysmentioning
confidence: 99%
“… 6 In particular, the combined use of OM-85 and vaccination was recognized as an effective approach to improve prevention strategies in order to reduce the burden of recurrent respiratory infections associated with wheezing episodes. 6 …”
Section: Recurrent Wheezing or Reactive Airwaysmentioning
confidence: 99%